The Identification of Genotype and Environmental Factors in Cleft Lip with/without Cleft Palate (Orofacial Cleft) Case - A Al-Ghazali - Nim: 10612061 , Zainab
Cleft lip with/without cleft palate (orofacial cleft) is a form of congenital defects that occurs most often in Asian racial group and its manifestation can be influenced by various genotypes and environmental factors. The information regarding the specific gene which can cause the orofacial cleft incident in the Asian group as well as the influencing environmental factors, however, has not been known for certain. The exposure to cigarettes smoke at the gestation period is one of the allegedly environmental factors that can trigger the incidence of orofacial cleft. In this study, the genotypes and environmental factors that can triggered the orofacial cleft in Asian region, especially Southeast Asia, was identified using Meta-Analysis. Meta-Analysis is a retrospective study method in form of quantitative and systematics statistical analysis of data from various relevant studies based on various parameters and has been screened from various scientific data base. This method can be used as an alternative method for studying the complex epidemiology and etiology of orofacial cleft. The quality assessment of the study that will be used in Meta-Analysis is conducted with Critical Appraisal Tools - Case Control Newcastle Ottawa Scale (NOS). The extracted data form the screened study was analysed with various statistical analysis methods, such as The Dersimonian and Laird random effect group analysis, Q-test, and I2 test. The result showed that there are at least five genes, TGFA, IRF6, MSX1, CDH1 and ARHGAP29, which are involved in the prevalence of orofacial cleft in Southeast Asia. The MSX1 gene is the dominant gene that caused the orofacial cleft incident in Southeast Asia because this gene has the highest effect size (0.44; CI 95% 0.1684-0.7214) with low data heterogeneity (11.14%). The analysis of the environmental factor influence on MSX1 gene showed a strong influence from maternal smoking to MSX1 gene in triggering the orofacial cleft incidence. The effect size between MSX1 gene and this factor is 0.2006 (CI 95% 0.1605-0.2406), with 0% data heterogeneity. Based on these results, it can be concluded that there are at least 5 types of gene involved in the emergence of orofacial cleft in Southeast Asia and maternal smoking is the environmental factors that strongly influence MSX1 gene in the orofacial cleft incident. This information can be essential in designing the study to prove the influence of environmental factors on orofacial cleft incident in Asian Region, especially Southeast Asia.